Biocorrosion detection by sulphur isotopic fractionation measurements. (1st April 2020) - Grousset, S.; Urios, L.; Mostefaoui, S.; Dauzeres, A.; Crusset, D.; Deydier, V.; Linard, Y.; Dillmann, P.; Mercier-Bion, F.; Neff, D.
Highlights: Iron sulphide are distributed at the micrometric scale in anoxic corrosion layers. Sulphur isotopic fractionation determine the biotic/abiotic origin of iron sulphide. δ 34 Ssulphides-sulphates is negative for iron sulphide of bacterial origin. δ 34 Ssulphides-sulphates is close to zero for iron sulphide of inorganic origin. NanoSIMS allows to measure the δ 34 S of sulphides at the submicrometric scale. Abstract: This innovative study presents a local diagnosis approach based on nanoSIMS technique to determine the biotic/abiotic origin of iron sulphides of (sub)micron size heterogeneously located in the corrosion product layers of iron. For iron coupons corroded in controlled conditions, negative δ 34 Ssulphides-sulphates were obtained in biotic conditions contrary to δ 34 Ssulphides-sulphates obtained in abiotic ones. These results underline that nanoSIMS is a reliable local technique to detect the formation origin of (sub)micron iron sulphides. This successful methodology was then applied to a complex system representative of an iron corroded in the conditions similar to those of radioactive wastes storage in geological medium.